Success Analysis of Flip: A Free Interbank Funds Transfer Mobile Application Using the UTAUT2 Model - Madek Jeani Purnama; Ni Putu Sri Harta Mimba; Maria M. Ratna Sari; Dodik Ariyanto (Jurnal Ilmiah Akuntansi, 2023)
The COVID-19 pandemic has profoundly influenced consumer behavior, leading to a surge in online transactions, particularly through social media platforms. However, transactions involving money transfers between different banks often incur fees, posing a challenge. The Flip application emerges as a viable solution, offering a novel approach to such transactions within the e-commerce landscape. Despite its relative novelty, the Flip application plays a significant role in addressing this challenge. Notably, there is a paucity of studies analyzing the success of this digital platform within the e-commerce domain. This research aims to bridge this gap by adopting the UTAUT2 model, extending it with the variables PR, PT, and SE. Employing accidental sampling, data were collected and analyzed using SEM-PLS. The study reveals that PE, SI, PV, and HAB significantly influence the intention to use Flip. These findings suggest that improving services in these areas can contribute to increasing the user base of the Flip application. This research not only adds to the understanding of digital application success but also provides actionable insights for Flip application system providers seeking to enhance user engagement.